1998
DOI: 10.1046/j.1365-2389.1998.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic matter and its parent organic matter in grass upland soil horizons studied by analytical pyrolysis techniques

Abstract: Summary We have sought to understand the molecular mechanisms by which dissolved organic matter (DOM) forms and soil organic matter (SOM) degrades in upland peaty gley soil under grass. Pyrolysis mass spectrometry (Py‐MS) and pyrolysis gas chromatography mass spectrometry (Py‐GC/MS) were applied to characterize the DOM collected from lysimeters and its parent SOM. The macromolecular organic matter in the litter and fermentation (Lf) horizon of the soil consists primarily of little decomposed lignocellulose fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 25 publications
5
38
0
Order By: Relevance
“…Probably peroxidase was the most important ligninolytic enzyme excreted by microorganism from the coniferous and broadleaf forest. Increased temperature appeared to result in great lignin degradation in organic matter (Huang et al 1998). Tuomela et al (2000) also found in compost experiment that the elevated temperatures were essential for rapid lignin degradation and the optimum temperature for thermophilic fungi and lignin degradation was 40-50°C.…”
Section: Discussionmentioning
confidence: 99%
“…Probably peroxidase was the most important ligninolytic enzyme excreted by microorganism from the coniferous and broadleaf forest. Increased temperature appeared to result in great lignin degradation in organic matter (Huang et al 1998). Tuomela et al (2000) also found in compost experiment that the elevated temperatures were essential for rapid lignin degradation and the optimum temperature for thermophilic fungi and lignin degradation was 40-50°C.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that the heterocyclic N is a significant component of the soil organic matter (e.g., Schulten and Schnitzer 1998), which may not be found from the solid-state 15 N nuclear magnetic resonance (NMR) analysis. Huang et al (1998), using Py-MS and Py-GC-MS to analyze dissolved organic mater from grassland soils, revealed that the dissolved organic matter showed a large accumulation of more oxidized lignin and aromatic structures, especially those containing carboxylic and dicarboxylic acid functionalities and with shorter side-chain length. Pyrolysis techniques have some limitations, including method effects such as cyclization and defunctionalization reactions in pyrolysis and variation in the yields of degradation by-products (Page et al 2002;Templier et al 2005).…”
Section: Pyrolysis-mass Spectrometrymentioning
confidence: 99%
“…Using analytical pyrolysis, Huang et al (1998) found that DOC was the most oxidized and microbially processed fraction of SOM. Kaiser and Guggenberger (2000) showed that the carbohydrate and lignin profiles of DOC most resembled that of C found in the clay fraction of the mineral soil, which is generally considered to be a highly altered biological reaction product.…”
Section: Introductionmentioning
confidence: 99%